IMPLEMENTASI KEBIJAKAN PENGARUSUTAMAAN GENDER (PUG) PADA BADAN PEMBERDAYAAN PEREMPUAN DAN KELUARGA BERENCANA KABUPATEN KUTAI TIMUR - Salasiah Salasiah (Prodi Ilmu Administrasi Negara, 2019)
The results of the research indicate that (1) the implementation ofPUG policy seen from the RPJMD prioritizes the improvement of women'scapacity and role in development, especially the participation of women in thegovernment, private sector, labor force and improvement of genderdevelopment index. While the PUG policy contained in BPPKB strategic planshows that the enactment of strategies such as increasing participation ofwomen in private institutions and government.There is a description of the activities that run optimally such as theExhibition of Women's Works in the Field of Development in addition thereare also activities that have not run optimally such as Building a WomenAwakening Activity in Politics, this activity needs to be maximized again byBPPKB. (2) the factors influencing the implementation of policies such asenvironmental conditions indicate that the community is still less concernedwith women's participation in public decisions and public policy.Then in the inter-organizational relationship factor, the action plan ofGender Mainstreaming (PUG) in each Unit of Regional Work Unit isimplemented in harmony so that requires cooperation between the SKPD andcross-sectoral involvement. Furthermore, the Resource factor shows that thequantity of women in BPPKB has more number than men. In addition, supportin the form of equipment and equipment is sufficient and the characteristicfactor of the implementing agency capability shows the commitment ofBPPKB employees in socializing gender responsive development.